Aggressive motivation mediates the influence of prosocial video game play on young children’s aggressive behavior - Li, Yan; Deng, Tao; Ngombe, Nicola; Kanske, Philipp (Frontiers in Psychology, 2025)
IntroductionAggressive behavior in early childhood can have lasting consequences. This study examined whether prosocial video game play can reduce aggressive behavior in relatively Chinese preschoolers and explored the mediating role of aggressive motivation and the moderating effects of age and gender.MethodsA total of 132 children aged 4 to 6 years (50% girls; M = 5.0, SD = 0.82) participated in a between-subjects experiment. Participants were randomly assigned to play either a prosocial or a neutral video game. Aggressive behavior and aggressive motivation were assessed following gameplay.ResultsChildren who played the prosocial video game exhibited significantly lower levels of aggressive behavior than those in the neutral game condition. Revenge motivation significantly mediated this effect. The mediating effect was stronger in boys than in girls; age did not moderate the associations.DiscussionThese findings suggest that prosocial video games may be effective in reducing aggressive behavior among preschoolers, partly by lowering revenge-related motivation. Gender differences in the mediation pathway highlight the need for tailored early interventions.